A situation analysis of sex education and communication and the implications thereof for HIV/AIDS prevention work - Mankayi, Andiswa (Rhodes University, Faculty of Humanities, Department of Psychology, 2003)
This study explores the history of sex communication and education over a period of fifty years (1950 to the present), in a deep rural area of the Eastern Cape. It describes patterns of sex communication between peers, between siblings, between children and parents and between young people and other non-familial agencies within communities. Communication trends are traced from the period before contraception was introduced, through to the introduction of female birth control methods into the HIV/AIDS era where the focus has been on attempting to introduce condoms. Twelve semi-structured interviews and two four-person focus groups were conducted to gather information on how the participants acquired information about sexuality and their responses to the same. The findings of the present study suggest that the widespread use of injectable contraceptives has had a marked effect on the sexual culture of the community under investigation. It has led to the collapse of the regulatory practices which were previously in place. This in turn has significantly affected the sexual communication and negotiation context. Furthermore, it has had a determining influence on male involvement in sexual reproductive health matters and has created a poor context for the adoption of condoms as a prophylactic. There were no major changes in the sexual communication context within families and within communities in that education has always been limited to instructions to avoid pregnancy. Of note was a culture of collusion between adults and children surrounding sexuality, which absolved the parties involved in addressing sexuality. These factors are understood have mediated response to HIV/AIDS prevention efforts, and need to be taken into consideration in the development of sex communication and education programmes.
Keywords: Sex instruction; Safe sex in AIDS prevention; AIDS (Disease) -- South Africa -- Eastern Cape; AIDS (Disease) -- South Africa -- Eastern Cape -- Prevention